Evaluating the Effects of a Targeted Home Visiting Program on Maternal and Child Health Outcomes - Malte Sandner; Thomas Cornelissen; Tanja Jungmann; Peggy Herrmann (Institute of Labor Economics (IZA), 2017)
We evaluate the effects of home visiting targeted towards disadvantaged first-time mothers on maternal and child health outcomes. Our analysis exploits a randomized controlled trial and combines rich longitudinal survey data with unique administrative health data. In a context in which the target group has comprehensive health care access, we find that home visiting has no effects on most types of health utilization, health behaviors, and physical health measures. However, the intervention has a remarkably robust and sizable positive effect on maternal mental health, reducing depressions reported in the survey data and prescriptions of psycholeptics recorded in the administrative data.
Keywords: I14; 330; child health; disadvantaged families; mental health; early childhood intervention